Institutions of deliberative democratic processes and interest groups: roles, tensions and incentives - Hendriks, Carolyn (2002)
There are inherent tensions between traditional, more pluralist forms of public participation and new deliberative democratic processes, such as citizens' juries. These innovative processes, known collectively as citizens ` forums, challenge existing roles and power relationships between interest groups and the state. Instead of having key access to the policy stage, interest groups are required to be `bystanders', `information providers', and ultimately `process legitimisers'. With such a radical shift in roles and power structure, there are few apparent reasons why interest groups would want to participate in such deliberative processes. In some cases, to the detriment of the process, they decide not to. - Reproduced.
Keywords: Interest groups; Policy making